2017
DOI: 10.1519/jsc.0000000000001855
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of the Association Between Physical Fitness and Musculoskeletal Injury Risk: Part 1—Cardiorespiratory Endurance

Abstract: Musculoskeletal injuries (MSK-Is) are a significant health problem for both military and athletic populations. Research indicates that MSK-I is associated with physical fitness; however, the association between specific components of physical fitness and MSK-I in military and athletic populations has not been systematically examined. Our goal was to systematically review the literature to provide a best evidence synthesis on the relationship between components of physical fitness and MSK-I risk in military and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
54
2
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(61 citation statements)
references
References 72 publications
1
54
2
4
Order By: Relevance
“…According to sports modality, multiple factors can be associated with the prevalence of injuries in athletes [1,8,22]. Despite the differences in dynamics, logic, mechanisms, goals and training style of various sports, studies have been shown non-modifiable and modifiable risks associated with the prevalence of types and locations of MSK-I in athletes [1,23,30].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…According to sports modality, multiple factors can be associated with the prevalence of injuries in athletes [1,8,22]. Despite the differences in dynamics, logic, mechanisms, goals and training style of various sports, studies have been shown non-modifiable and modifiable risks associated with the prevalence of types and locations of MSK-I in athletes [1,23,30].…”
Section: Discussionmentioning
confidence: 99%
“…Musculoskeletal injuries (MSK-I) are some of the most severe health problems in sports medicine, resulting in high economic costs, withdrawal of athletes from training and competitions and potentially affecting athlete performance [1]. The prevalence of injury types and locations is different according to sport modality, varying from 5 to 60% for joint injuries [2,3], 20-60% for muscle injuries [4,5] and 10-50% for tendinopathy [6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A prática do Pilates como exercício regular pode beneficiar o indivíduo idoso em diversos fatores, como contribuir para o aumento da capacidade funcional e melhora na qualidade de vida, além de, como exercício físico contínuo, levar a uma melhor aptidão física 8 . Essa melhora é citada como uma das necessidades básicas para conseguir manter a saúde em condições adequadas 9 , o que é de extrema importância no processo de envelhecimento.…”
Section: Introductionunclassified
“…In particular, there is strong evidence that poor performance on a timed run test with a fixed distance is a predictor for such injuries [6]. …”
Section: Introductionmentioning
confidence: 99%